Anselm, the Holy Trinity, and the Relative Identity Thesis - Conn, Christopher Hughes (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2019)
Anselm’s On the Incarnation of the Word is presented as a letter to Pope Urban II for the purpose of exposing and correcting the theological errors of Roscelin of Compiègne, who maintained that since only the Son became incarnate, we must conclude that the Father, the Son and the Holy Spirit are numerically distinct substances. In this paper I argue that Anselm’s rejection of this conclusion involves an account of the Holy Trinity which includes a strongly relativized conception of identity, that is, one which allows an object x and an object y to be the same F, but different Gs. I further contend that Anselm buttresses this account with two non-theological examples of relative identity. Although it may well be the case that advocates of Latin Trinitarianism are generally committed to such an account, since they affirm that the Father is the same substance as the Son but not the same person as the Son, I take Anselm’s defense of this position to be theologically significant, first, because it may well be the first explicit defense of Relative Trinitarianism, and second, because Anselm’s position as a bishop and a Doctor of the Church is (for Catholics, at least) an indication of its theological soundness.